PENGARUH KNOWLEDGE SHARING, STANDAR SOP TUGAS TERHADAP KINERJA PEGAWAI PUSKESMAS KOTO BARU - Mayroza Wiska; Kelik Purwanto; Titania Putri Utami (Indonesian Journal of Thousand Literacies, 2023)
Health Center Employees This study was conducted to find out what kind of impact is caused by the influence of Knowledge sharing and Standard Operating Procedures on Tasks on Employee Performance at the Koto Baru Public Health Center. The purpose of this study was to identify and analyze as well as to determine the effect of Knowledge sharing and Standard Operating Procedures on the Performance of Employees at Koto Baru Health Center. The method of analysis in this study is a quantitative method using a questionnaire. The population in this study were 126 respondents and the samples in this study were 126 who were employees at the Koto Baru Public Health Center. The method in this study is non-probability sampling, and the research method is the census method. In addition, there is a positive and significant influence between the variables of Standard Operating Procedures and Tasks on employee performance among employees at the Koto Baru Health Center. Based on the results of the F test, it was found that Knowledge Sharing (X1) and Standard Operating Procedures (X2) had a significant simultaneous effect on employee performance (Y). The results of the R test show that the Adjust R Square is 0.707, this indicates that the contribution of the knowledge sharing variable and standard operating procedures on the task to employee performance is 0.707. which means that the influence of knowledge sharing variables and standard operating procedures on employee performance is 70.7% while 29.3%